The strengthening of U.S - Vietnam. Relations with the rise of China (2014)
Since the defeat of the United States in the Vietnam War, relations between the two countries were minimal until 1945, when diplomatic relations were restored. The rise of China as an important actor in Asia Pacific has captured the attention of the Obama administration, which considers this region as a geostrategic priority for the United States. This situation has generated a change in policy. The United States has made efforts to strengthen ties with Vietnam as a strategy to counterbalance hegemony in the region, and thus maintain its influence in the Asia Pacific.